A proof of some Schützenberger-type results for Eulerian paths and circuits on digraphs - Byoung-Song Chwe (International Journal of Mathematics and Mathematical Sciences)
This paper shows that the number of even Eulerian paths equals the number of odd Eulerian paths when the number of arcs is at least twice the number of vertices of a digraph.